Breeding Urochloa and Megathyrsus forage grasses for low methane livestock systems - Barbosa Torres, Norma; Garzon, Maria Jose; Mejía, Juan Camilo; Mazabel, Johanna; Marin, Alejandra; Molina, Isabel; Arango, Jacobo; Jauregui, Rosa Noemi (2025)
Ruminant livestock is the primary global source of meat and milk, efficiently transforming vegetative material into human-edible protein. Agricultural grasslands cover two-thirds of the Earth's agricultural land, dominated in the tropics by forages of the genera Urochloa and Megathyrsus supporting over 1 billion animals. Livestock plays a vital economic and social role. However, inadequate feed quality and management negatively impact both environmental sustainability and livestock productivity. This study aims to develop low-methane forages (LMF) to mitigate greenhouse gas emissions from livestock by introducing traits that will reduce enteric methane production into widely used forage-grass cultivars through conventional breeding methods. The LMF strategy focuses on highly digestible forages that minimize methane production per unit of dry matter digested, incorporating potentially anti-methanogenic compounds. Methodology: The Alliance of Bioversity International and CIAT is evaluating elite genotypes and commercial cultivars from three breeding programs: Interspecific Urochloa, Megathyrsus maximus and Urochloa humidicola selected for agronomic performance and seed yield potential as a measure of scalability and environmental adaptation. In 2024 three separate field trials were established, one for each species of interest, in and alpha lattice with three reps and 5 plants per rep. These lines are being assessed for key agronomic traits such as forage production and nutritional quality including acid detergent fiber (ADF), neutral detergent fiber (NDF), truly digested dry matter (TDDM) and in vitro methane production (ml/g DM). The methane production and nutritional quality characterization started in 2025 and will continue until 2026. In 2025, three replicates per genotype (10 interspecific Urochloa genotypes, 35 Megathyrsus maximus, and 10 Urochloa humidicola) were sampled at the recommended height for each species. For the in vitro determination of methane production using the syringe methodology each sample was repeated three times resulting in a total of 9 replicates per genotype. Additionally, for each genotype tested, two sub-samples were freeze-dried and stored for future genomics and metabolomics studies. Preliminary results in terms of methane production indicated that the Urochloa interspecific genotypes sampled had an average 25.9 ± 6.7 CH4 ml/g DM incubated for 24 h, data less than 30 ml/g DM; in addition, TDDM shows 64.1%± 2.1 close to 70%. Regarding Nutritional Quality fiber traits obtained DFN 57.8% and ADF 23.3% that added together was less 100%. There are significant differences between genotypes on each genera Tukey p<0.05. U. humidicola genotypes sampled had an average 36.0 ± 3.3 CH4 ml/g DM, data more than 30 ml/g DM; in addition, TDDM shows 57.2%± 2.2 close to 70%. Regarding Nutritional Quality fiber traits obtained DFN 68.4% and ADF 29.1% that added together was less 100%. Megathyrsus maximus genotypes sampled had an average 30.2 ± 4.6 CH4 ml/g DM, data near to 30 ml/g DM; in addition, TDDM shows 57.9%± 3.7. Regarding Nutritional Quality fiber traits obtained NDF 65.3% ADF 29.8% that added together was less 100%. Once the remaining genotypes are sampled, the best genotypes will be selected using a decision matrix prioritizing low CH4 production, high TDDM, nutritional quality parameters, agronomic performance and scalability.